DESIGN AND BUILD OF AICAT 3D SIMULATOR FOR CARING CAT USING STATE-BASED BEHAVIOR METHOD - Emilisa
Ignorance of how to care for cats can have a devastating effect on it. In an effort to avoid unwanted things, there is a need for educational media regarding guidelines for raising cats for the community. Technology-based games (game) are considered as the best media to be used as a learning medium. Game-based learning gets better learning outcomes compared to other learning media which is only one way. Based on that, game-based learning can also be used as a strategy for the simulation learning method. State-Based Behaviors are the most suitable method for making artificial intelligence systems in simulations compared to the pathfinding method which is useful for NPCs who are moving from one location to another and Strategy and Planning which is usually used for strategy games (RTS). Unlike Moar which only has four parameters, while AICat 3D has 7 parameters used, namely Hungry, Poop, Pee, Thirsty, Happiness, Health, and Cleanliness. By using a simple behavior model, an interaction is made according to the state that effects the value of discipline. There are 4 types of discipline, namely Discipline Hungry, Discipline Happiness, Discipline Cleanliness, and Social. Testing was carried out on 30 users. Testing was done by giving questionnaires before and after playing AICat 3D for 7 days. The results showed that 73.3% (22 of 30 participants) experienced an increase in rank and the average number of questions answered before using AICat 3D was 7.467 to 9.9. so it can be concluded that AICat 3D can be implemented as a learning medium because it provides an increase in knowledge participants how to raise a cat well and properly. Besides that, the calculation of the Wilcoxon signed rank test with a p-value of 0.000185 is less than the critical research limit of 0.05, which means that it has a significant effect between before and after using this AICat 3D simulation system.